Soap composite particles, method for manufacturing soap composite particles, and cosmetic
Patent Information
- Application Number
- KR1020267013332
- Authority / Receiving Office
- KR · KR
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-12-26
- Filing Date
- 2024-08-20
- Publication Date
- 2026-09-01
Smart Images

Figure PCT00001 
Figure PCT00002 
Figure PCT00003
Abstract
Description
Technology Field
[0001] The present invention relates to soap composite particles, a method for manufacturing soap composite particles, and a cosmetic composition. Background Technology
[0002] Patent Document 1 discloses a metal soap and a method for manufacturing the same, which can improve the anti-caking properties, fluidity, or texture of a powder by imparting high dispersibility or coating properties to the powder. This metal soap is characterized by having an internal introduction rate (A), defined as the ratio of an inorganic crystal nucleating agent introduced into the interior of the metal soap particles, of 30% or more. Prior art literature
[0003] Patent Document 1: Japanese Patent Publication No. 6729546 The problem to be solved
[0004] Patent Document 1 suggests that the particle shape becomes uniform and the particle size distribution becomes sharp due to the function of an inorganic crystal nucleating agent introduced into the interior of metal soap particles, and as a result, the solid powder cosmetic of the example has a good texture. However, Reference Document 1 does not describe or suggest the compatibility of the improvement of skin texture and the sustainability of the function of the soap composite particles.
[0005] If the cosmetic product contains paraffinic solvents such as isododecane, there is a concern that it may affect the sustainability of the function of metal soap particles compared to silicone-based solvents such as dimethicone.
[0006] The present invention has been made in consideration of the above circumstances and aims to provide a soap composite particle capable of achieving both improvement of skin texture and sustainability of the function of the soap composite particle, a method for manufacturing said soap composite particle, and a cosmetic composition containing said soap composite particle. means of solving the problem
[0007] A first aspect of the present invention is a soap composite particle having a core particle containing a saturated higher fatty acid salt and an inorganic oxide externally added to the core particle, wherein the total content of Li2O, Na2O, Al2O3, MgO, CaO, ZnO, BaO, TiO2, SiO2, Fe3O4, Fe2O3, and FeO in the core particle is 0 to 15 mass%, and the shape of the core particle is spherical with a sphericity of 0.80 to 1.00.
[0008] In the second embodiment, the carbon number of the saturated higher fatty acid salt is in the range of 10 to 20, in the first embodiment.
[0009] In the third embodiment, in the first or second embodiment, the metal forming the saturated higher fatty acid salt is one or more of Li, Na, Al, Mg, Ca, Zn, and Ba.
[0010] The fourth embodiment is an embodiment of any one of the first to third embodiments in which the amount of the inorganic oxide added to 100 parts by weight of the core particle is 0.01 to 15 parts by weight.
[0011] The fifth embodiment is one of the first to fourth embodiments in which the inorganic oxide is one or more of zinc oxide, magnesium oxide, titanium dioxide, mica, talc, kaolin, sericite, silica, iron oxide, alumina, zirconia, and zeolite.
[0012] The sixth embodiment is in any one of the first to fifth embodiments, wherein the inorganic oxide is hydrophobized.
[0013] The seventh embodiment is the sixth embodiment in which the hydrophobization treatment is any one of silane coupling treatment, silicone oil treatment, long-chain alkyl silane treatment, fatty acid salt treatment, long-chain alkane treatment, long-chain alkene treatment, and long-chain alkyne treatment.
[0014] The eighth embodiment is one of the first to seventh embodiments in which the average primary particle size of the inorganic oxide is 0.01 to 1.0 μm.
[0015] The ninth embodiment is an embodiment of any one of the first to eighth in which the volume-based median diameter of the core particle is greater than 3 μm and less than 20 μm.
[0016] The 10th embodiment is a method for manufacturing soap composite particles of any one of the 1st to 9th embodiments, comprising a grinding process for grinding a solid of a saturated higher fatty acid salt, a spheroidization process for spheroidizing the particles obtained by the grinding process, and an exfoliation process for exfoliating an inorganic oxide to the core particles obtained by the spheroidization process.
[0017] The eleventh embodiment is a method for manufacturing soap composite particles of any one of the first to ninth embodiments, comprising a grinding process for grinding a solid of a saturated higher fatty acid salt, an exfoliation process for exfoliating an inorganic oxide to the particles obtained by the grinding process, and a spheroidization process for spheroidizing the particles obtained by the exfoliation process.
[0018] The 12th embodiment is a cosmetic composition characterized by incorporating soap composite particles of any one of the 1st to 9th embodiments. Effects of the invention
[0019] According to the present invention, it is possible to provide soap composite particles capable of achieving both improved skin texture and sustained function of the soap composite particles, a method for manufacturing said soap composite particles, and a cosmetic composition containing said soap composite particles. Specific details for implementing the invention
[0020] The present invention is described below using embodiments, but these embodiments are described in detail to better facilitate understanding of the well-known aspects of the invention and do not limit the invention unless specifically stated otherwise. Other embodiments in which the configurations of the following embodiments are appropriately substituted by those skilled in the art are also included within the scope of the present invention.
[0021] The soap composite particle of the present embodiment has a core particle containing a saturated higher fatty acid salt and an inorganic oxide externally added to the core particle.
[0022] Saturated higher fatty acid salts
[0023] The core particles contain a saturated higher fatty acid salt. The saturated higher fatty acid salt may be an alkali metal salt such as sodium or potassium, or a metal salt other than an alkali metal salt. The saturated higher fatty acid salt may be manufactured by commercial methods using saturated higher fatty acids or their alkali metal salts and inorganic metal salts as raw materials, or a commercially available product may be used. The saturated higher fatty acid salt may be a single type or a mixture of two or more types.
[0024] The saturated higher fatty acids used in the above saturated higher fatty acid salts are not particularly limited, but hexanoic acid, caproic acid (n-hexanoic acid), heptanoic acid, octanoic acid, caprylic acid (n-octanoic acid), nonanoic acid, decanoic acid, capric acid (n-decanoic acid), lauric acid, myristic acid, palmitic acid, stearic acid, arachinic acid, behenic acid, montanic acid, etc. are suitable.
[0025] Saturated higher fatty acids have high chemical stability because they do not have double bonds (unsaturated bonds) in their hydrocarbon chains, and they are resistant to degradation by oxygen or ultraviolet rays, making it easy to maintain excellent quality. Although the saturated higher fatty acid salt may be branched, it is preferable for the saturated higher fatty acid salt to have two or fewer carbon atoms included in the branched side chains, and it is more preferable for the saturated higher fatty acid salt to have one or fewer carbon atoms. Straight-chain saturated higher fatty acid salts are particularly preferred.
[0026] When the above-mentioned saturated higher fatty acid salt is a straight-chain saturated higher fatty acid salt, the structure is stable because the hydrocarbon chain does not have double bonds (unsaturated bonds) or side chains. In addition, the methyl groups at the molecular ends are uniformly arranged on the surface of the soap composite particles, and furthermore, because the melting point is high, it is difficult to become liquid at room temperature (5 to 35°C), making it easy to maintain excellent quality.
[0027] The number of carbon atoms in the above-mentioned saturated higher fatty acid salt is not particularly limited, but, for example, may be within the range of 8 to 30, preferably within the range of 10 to 20, more preferably within the range of 10 to 18, and particularly preferably within the range of 10 to 16. When the number of carbon atoms is above the lower limit, the saturated higher fatty acid salt exhibits hydrophobicity and becomes less susceptible to moisture. When the number of carbon atoms is below the upper limit, the molecules become easier to align, the structure becomes stable, the melting point increases, and the shape of the core particles is stabilized. Furthermore, the sustainability of the function of the inorganic oxide is improved.
[0028] The metal salts used for the above-mentioned saturated higher fatty acid salts are not particularly limited, but examples include alkali metal salts, alkaline earth metal salts, and transition metal salts. As metals forming the saturated higher fatty acid salts, one or more of Li, Na, Al, Mg, Ca, Zn, and Ba may be used; preferably, one or more of Zn, Mg, Ca, and Al are used; and more preferably, one or more of Zn, Mg, and Ca are used. These compounds form a stable structure in the soap itself. Among these, it is desirable to select a compound that has minimal impact on the human body and is insoluble in water.
[0029] In particular, for a composition containing the above-mentioned soap composite particles to be applied to the skin, it is desirable that the molecular ends of the saturated higher fatty acid salts form a uniform hydrophobic surface. Accordingly, the skin texture is improved as it is less affected by moisture in the air or moisture in body fluids such as sweat. Examples of uses for the composition applied to the skin include cosmetics, pharmaceuticals, and other drugs.
[0030] The above-mentioned saturated higher fatty acid salt has a carboxylate ion group (-COO) at one end. -It is desirable that it does not contain polar functional groups such as hydroxyl groups or epoxy groups, except for having ). Accordingly, hydrophobicity is improved. The general formula of a saturated higher fatty acid salt is (RCOO) m When denoted as M, at least some or all of the saturated higher aliphatic group R is C n-1 H 2n-1 It is preferable that it be an acyclic alkyl group represented by -, and CH3(CH2) n-2 It is preferable that it be a straight-chain alkyl group represented by -. As for the branched alkyl group, it is preferable that the branch is located away from the carboxylate ion group, for example, (CH3)2CH(CH2) n-4 - can be cited. General formula (C n-1 H 2n-1 COO) m It is preferable to include an acyclic compound represented by M, and the general formula [CH3(CH2) n-2 COO m It is more preferable to include straight-chain compounds denoted by M. In these general formulas, n represents the number of carbon atoms, and M represents a metal.
[0031] When the metal (M) of the above-mentioned saturated higher fatty acid salt is a multivalent group, that is, when m is 2 or more, the number of carbon atoms (n) of the m saturated higher fatty acids may be the same or different. When the number of carbon atoms (n) of the m are different, it is preferable that the difference between the maximum number of carbon atoms and the minimum number of carbon atoms is 4 or less, and more preferable that it is 2 or less. In order for the molecular ends of the saturated higher fatty acid salt to form a more uniform hydrophobic plane, it is preferable that the number of carbon atoms of each saturated higher fatty acid constituting the saturated higher fatty acid salt be the same.
[0032] Core Particle
[0033] The shape of the core particles is spherical with a circularity of 0.80 to 1.00. It is more preferable that the circularity of the core particles be 0.90 to 1.00. The saturated higher fatty acid salt of the core particles acts as a lubricant, making it easy to roll without resistance. If the circularity of the core particles is greater than or equal to the lower limit value, the particles are more likely to roll and slide without resistance. For example, when a composition containing soap composite particles is applied to the skin using a fingerprint, the particles roll easily, thereby providing a favorable effect on the skin. The theoretical maximum value of the circularity is 1, which is the case where the particle shape is truly spherical.
[0034] The circularity can be obtained by analyzing the particle shape to measure the area (A) and the periphery (C) of the particle shape, and by setting the diameter of the circle (circle equivalent diameter) equal to the area (A) of the particle shape (circle equivalent diameter) as D and the circumference as π, from the following formula.
[0035] (Circularity) = πD / C
[0036] As a method for measuring the sphericity of particles, for example, a flow-type particle analysis device may be used to measure particle shape, particle size distribution, particle number, etc., by two-dimensional image analysis of a particle group. In addition, the sphericity may be calculated by observing the surface of the particles from multiple fields of view using an electron microscope and performing three-dimensional image analysis.
[0037] In the soap composite particles of the present embodiment, the total content of Li2O, Na2O, Al2O3, MgO, CaO, ZnO, BaO, TiO2, SiO2, Fe3O4, Fe2O3, and FeO in the core particles is 0 to 15 mass%. These metal oxides (hereinafter referred to as "specific metal oxides") may originate from inorganic oxides externally added to the core particles, may originate from inorganic oxides internally added to the core particles, or may originate from saturated higher fatty acid salts. The specific metal oxides may be different from the inorganic oxides externally added to the core particles, or may be different from the inorganic oxides internally added to the core particles.
[0038] In cases where the above-mentioned core particles do not contain a specific metal oxide, it is preferable that inorganic oxides are not added to the core particles, or that inorganic oxides different from the specific metal oxides are added. In this case, the content of the specific metal oxide in the core particles (total content) may be 0 weight%, but there may be cases where the specific metal oxide is incorporated into the core particles as an impurity, or where a portion of the inorganic oxides added to the core particles are included in the core particles.
[0039] In cases where the above-mentioned core particles contain a specific metal oxide, it is preferable that the inorganic oxide added to the core particles contains the specific metal oxide. In this case, it is preferable that the content of the specific metal oxide in the core particles (total content) be 0.01 weight% or more.
[0040] Among them, when a specific metal oxide is Al2O3, MgO, ZnO, TiO2, SiO2, Fe3O4, Fe2O3, or FeO, and also serves as an inorganic oxide having desirable functionality that is externally or internally added to the core particles, the content is preferably 0.01 weight% or more. Accordingly, the function of the inorganic oxide is expressed and the sustainability is improved.
[0041] The metal included in the specific metal oxide (Li, Na, Al, Mg, Ca, Zn, Ba, Ti, Si, Fe) may be the same as the metal forming the saturated higher fatty acid salt (preferably Li, Na, Al, Mg, Ca, Zn, Ba). Since the content of the specific metal oxide in the core particle is below the upper limit value, the crystallinity of the saturated higher fatty acid salt is easily maintained. Accordingly, the shape of the core particle is easily maintained, and the skin feel is improved. When the metal included in the specific metal oxide and the metal forming the saturated higher fatty acid salt are each selected from the group consisting of Li, Na, Al, Mg, Ca, Zn, and Ba, different metals may be selected.
[0042] The volume-based median diameter of the core particles is preferably greater than 3 μm and less than 20 μm, more preferably greater than 5 μm and less than 15 μm, and even more preferably greater than 7 μm and less than 10 μm. If the volume-based median diameter of the core particles exceeds the lower limit value, the cohesive force of the particles decreases, making it difficult to form a lump shape. If the volume-based median diameter of the core particles is less than the upper limit value, the surface area per unit weight increases and the exposed surface area of the inorganic oxide increases, thereby improving the sustainability of the function of the inorganic oxide.
[0043] When a composition containing the above soap composite particles is applied to the skin, if the median diameter based on volume of the core particles exceeds the lower limit value, it spreads easily on the skin, allowing for a uniform skin texture upon application. Additionally, if the median diameter based on volume of the core particles is less than the upper limit value, it becomes difficult to feel the rough sensation caused by particle size with the fingertips, thereby improving the skin texture.
[0044] Inorganic oxides
[0045] The soap composite particles of the embodiment have an inorganic oxide externally added to the core particles. As described above, the core particles are not particularly limited as long as they have a structure containing a saturated higher fatty acid salt, but an inorganic oxide may be internally added to the core particles. The inorganic oxide internally added to the core particles may be embedded within the core particles. It is preferable that the inorganic oxide externally added to the core particles covers at least a portion of the outer surface of the core particles.
[0046] Examples of the above inorganic oxides include inorganic particles such as metal oxides, metal nitrides, silicates, sulfates, carbonates, and phosphates. Specific examples of inorganic oxides include one or more of zinc oxide, magnesium oxide, titanium dioxide, mica, talc, kaolin, sericite, silica, iron oxide, alumina, zirconia, and zeolite.
[0047] It is preferable that the above-mentioned inorganic oxide particles be functional particles. As for the functionality, it is preferable that the inorganic oxide particles act on the target object together with the saturated higher fatty acid salt when using the soap composite particles. Specific examples of the functionality are not particularly limited, but may include ultraviolet reflectivity, ultraviolet blocking properties, opacity as a pigment, anti-inflammatory properties against inflammation, X-ray absorption properties, solid lubricity, mold release properties, antibacterial properties, electrical insulation properties, etc.
[0048] The content of inorganic oxides in soap composite particles (total amount of internal and external additives) is preferably 3 to 80 weight percent. If the above total amount is greater than or equal to the lower limit, the exposed surface area of the inorganic oxide increases, thereby improving the sustainability of the function of the inorganic oxide. If the above total amount is less than or equal to the upper limit, the bonding between the saturated higher fatty acid salt and the inorganic oxide becomes stable, thereby improving the uniformity of the soap composite particles.
[0049] The content (inherent amount) of inorganic oxide in the core particles is preferably 5 to 75 weight%, and more preferably 5 to 10 weight%. If the above-mentioned internal amount is greater than or equal to the lower limit, the exposed surface area of the inorganic oxide increases, thereby improving the sustainability of the function of the inorganic oxide. If the above-mentioned internal amount is less than or equal to the upper limit, the mixing of the saturated higher fatty acid salt and the inorganic oxide becomes easier, thereby improving the uniformity of the core particles.
[0050] The amount of inorganic oxide added to 100 parts by weight of the core particles is preferably 0.01 to 15 parts by weight, and more preferably 0.05 to 8.0 parts by weight. If the amount of added inorganic oxide is greater than or equal to the lower limit, the amount of inorganic oxide present on the surface of the core particles increases, thereby improving the sustainability of the function of the inorganic oxide. If the amount of added inorganic oxide is less than or equal to the upper limit, the activity and tactile properties characteristic of saturated higher fatty acid salts become more superior.
[0051] The inorganic oxide added externally to the core particle may be an inorganic oxide of the same type as the inorganic oxide added internally to the core particle, or it may be a different inorganic oxide. The inorganic oxide added internally to the core particle may be one type or two or more types. If two or more types of inorganic oxides are added internally to the core particle, the amount added internally may be the total amount of two or more types. The inorganic oxide added externally to the core particle may be one type or two or more types. If two or more types of inorganic oxides are added externally to the core particle, the amount added externally may be the total amount of two or more types.
[0052] An inorganic oxide externally added to the core particles may function as a fluidity enhancer. In this case, the fluidity enhancer exerts a bearing effect, increasing the fluidity of the soap composite particles and improving the skin texture. As for the inorganic oxide externally added to the core particles, particles having a different function from the particles functioning as a fluidity enhancer may be used in combination.
[0053] The inorganic oxide externally and / or internally added to the core particles may be coated, for example, hydrophobically treated. The hydrophobically treated method is not particularly limited, but may include any one of silane coupling treatment, silicone oil treatment, long-chain alkyl silane treatment, fatty acid salt treatment, long-chain alkane treatment, long-chain alkene treatment, or long-chain alkyne treatment. For silicone oil treatment, modified silicone oil may be used.
[0054] In the case of silane coupling or silicone oil treatment, siloxane bonds are formed and immobilized on the surface of the inorganic oxide through the hydrolysis and dehydration condensation reactions of the silane coupling agent or silicone oil, and the inorganic oxide becomes hydrophobic. For this reason, the inorganic oxide exhibits high dispersibility even when kneaded at high temperatures in soap composed of hydrophobic higher saturated fatty acid salts.
[0055] In the case of fatty acid salt treatment, the composition of the fatty acid salt is identical or similar to the composition of the higher saturated fatty acid salt used in soap. For this reason, inorganic oxides surface-treated with fatty acid salts have high dispersibility within the blended soap and high adhesion to the soap. Furthermore, if the fatty acid salt used for the treatment corresponds to the aforementioned higher saturated fatty acid salt, that amount of mass may be subtracted from the mass of the inorganic oxide and added to the mass of the higher saturated fatty acid salt.
[0056] In the case of long-chain alkyl silane treatment, long-chain alkane treatment, long-chain alkene treatment, and long-chain alkyne treatment, inorganic oxides can be hydrophobized by using a long-chain aliphatic compound corresponding to each. The chain length in these long-chain aliphatic compounds is not particularly limited, but, for example, may be 8 to 30 carbon atoms.
[0057] It is preferable that the average primary particle size of the inorganic oxide externally and / or internally added to the core particles be 0.01 to 1.0 μm. If the average primary particle size of the inorganic oxide is greater than or equal to the lower limit above, the particles of the inorganic oxide are difficult to aggregate and are easy to disperse. In particular, when such inorganic oxide is externally added, the skin texture of the soap composite particles improves. If the average primary particle size of the inorganic oxide is less than or equal to the upper limit above, the inorganic oxide is easy to internally add to the core particles, and even when externally added, it is difficult for it to detach from the soap composite particles. In particular, when such inorganic oxide is externally added, the rough feeling (surface roughness caused by particles) of the inorganic oxide is reduced, and the skin texture of the soap composite particles improves.
[0058] Method for manufacturing soap composite particles
[0059] The soap composite particles of the present embodiment can be manufactured, for example, through a grinding process of saturated higher fatty acid salts, an exfoliation process of exfoliating an inorganic oxide to the core particles, and a spheroidization process of the core particles. The spheroidization process can be performed before or after the exfoliation process.
[0060] A manufacturing method in which a spheroidization process is performed before an external addition process preferably comprises a grinding process for grinding solids of saturated higher fatty acid salts, a spheroidization process for spheroidizing particles obtained from the grinding process, and an external addition process for externally adding an inorganic oxide to core particles obtained from the spheroidization process.
[0061] A manufacturing method in which a spheroidization process is performed after an external addition process preferably comprises a grinding process for grinding solids of saturated higher fatty acid salts, an external addition process for externally adding an inorganic oxide to the particles obtained from the grinding process, and a spheroidization process for spheroidizing the particles obtained from the external addition process.
[0062] When inorganic oxides are incorporated into the core particles, it is preferable to have a mixing process in which a mixed powder of saturated higher fatty acid salts and inorganic oxides is melted and kneaded before the grinding process. When inorganic oxides are not incorporated into the core particles, it is preferable to obtain a solid of saturated higher fatty acid salts by heating and melting the saturated higher fatty acid salts.
[0063] When inorganic oxides are added to core particles, prior to the mixing process, a weighing process may be performed to weigh the saturated higher fatty acid salt and inorganic oxide used in the production of core particles, and a mixing process may be performed to mix the weighed saturated higher fatty acid salt and inorganic oxide by stirring. Although not particularly limited, mixing devices such as double cone mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, and Nauta mixers may be used.
[0064] While it is possible to mix a portion of the raw materials during the kneading process, it is preferable to pre-mix at least a portion of the raw materials before the kneading process. Pre-mixing is suitable for controlling the composition of saturated higher fatty acid salts and inorganic oxides, as well as particle dimensions and shapes.
[0065] It is preferable to carry out the mixing process under conditions where the saturated higher fatty acid salt melts or softens due to heating. Accordingly, an inorganic oxide mixed with the saturated higher fatty acid salt is added to the saturated higher fatty acid salt. A batch mixer or a continuous mixer may be used. The mixer is not particularly limited, but examples include open rolls, kneaders, pressure kneaders, Banbury mixers, single-screw extruders, and twin-screw extruders. The heating temperature during the mixing process can be appropriately set according to the melting point of the saturated higher fatty acid salt, but examples include 80 to 250°C, 100 to 200°C, or 100 to 140°C.
[0066] When performing a kneading process of saturated higher fatty acid salts and inorganic oxides or a melting process of saturated higher fatty acid salts prior to the grinding process, it is desirable to carry out a cooling process to cool the mixture obtained from the kneading process or the melt obtained from the melting process. Excess heat may be absorbed by a cooling member in contact with the mixture or melt, such as by passing the molten mixture or melt through a cooling roll. The cooling member, such as the cooling roll, may contain a refrigerant such as cooling water inside. During the cooling process, it is also possible to dissipate heat from the mixture by means of air cooling, blowing, etc.
[0067] The grinding process may be carried out in multiple stages, such as a coarse grinding process and a fine grinding process. The device used for coarse grinding of particles is not particularly limited, but crushers, hammer mills, feather mills, cutter mills, etc., may be used. The device used for fine grinding of particles is not particularly limited, but jet mills, counter-jet mills, high-speed rotor mills, etc., may be used.
[0068] When grinding the above solids to a desired particle size, the particle size may be adjusted by a classification process as needed. For the classification process, for example, an inertial classification type elbow jet classifier, a centrifugal classification type Microflex, or an airflow classifier may be used. Particles coarser than the desired particle size may be returned to the grinding process for further grinding. Particles finer than the desired particle size may be returned to a kneading process or a melting process for reuse, depending on the composition.
[0069] The spheroidization process is a process of spheroidizing particles by heating. While the spheroidization device is not particularly limited, examples include devices that mechanically adjust particle shape, such as impact spheroidization devices; devices that adjust particle shape by dissolving binders and desoldering agents, such as spray dryers; and devices that adjust particle shape by heating in a medium or using hot air. If the spheroidization process is performed before the exfoliation process, spherical core particles can be obtained through the spheroidization process. If the spheroidization process is performed after the exfoliation process, soap composite particles in which the core particles have become spherical can be obtained. If necessary, it is also possible to perform a classification process after the spheroidization process.
[0070] The external addition process involves adding inorganic oxide to the core particles by mixing the inorganic oxide with the core particles. For the external addition process of inorganic oxide, a mixing device such as a super mixer or a Henschel mixer may be used, or a powder processing device such as a mechanomil may be used.
[0071] Soap Composite Particles
[0072] The soap composite particles of the embodiment can be used as various functional materials because they possess functionality provided by internally or externally added inorganic oxides in addition to the function of saturated higher fatty acid salts. The uses of the soap composite particles are not particularly limited, but examples include use as texture improvers, lubricants, lubricants, release agents, anti-caking agents, cosmetic raw materials, coloring agents, processing aids, dispersants, and additives.
[0073] Analysis Method of Soap Compound Particles
[0074] As described above, the soap composite particle of the embodiment comprises a core particle containing a saturated higher fatty acid salt and an inorganic oxide externally added to the core particle. Since the core particle is primarily composed of a saturated higher fatty acid salt, it is possible to separate the saturated higher fatty acid salt and the inorganic oxide. Accordingly, even if the inorganic oxide internally added to the core particle and the inorganic oxide externally added to the core particle are the same material, it is possible to evaluate the internal and external amounts.
[0075] As a specific example of a method for separating core particles and excipients (excipient inorganic oxides), a method may be used in which a probe of an ultrasonic homogenizer is inserted into a dispersion obtained by adding a pre-weighed powder of soap composite particles to a dispersion medium and ultrasonic waves are applied. Accordingly, excipients detached from the core particles can be suspended in the dispersion medium. After the core particles are settled by settling, centrifugation, etc., the supernatant in which excipients are suspended can be extracted and separated by liquid separation operations, etc.
[0076] The dispersion medium is preferably an aqueous solution prepared by dissolving a surfactant in water to inhibit the aggregation of the powder. Since saturated higher fatty acid salts are insoluble in water, the added inorganic oxides can remain contained within the core particles.
[0077] The amount of core particles from which the external additive has been separated can be weighed by drying the precipitate after repeating solvent washing and filtration using filter paper capable of capturing the core particles. Regarding the capturing performance of the filter paper, it is desirable to maintain particles of, for example, 1 μm or larger. The amount of the external additive may also be calculated by subtracting the mass of the core particles obtained by weighing from the mass of the soap composite particles.
[0078] The components and composition of the external additives included in the supernatant can be analyzed, for example, by X-ray fluorescence analysis (XRF) of the supernatant.
[0079] The components and composition of the inorganic oxides added to the core particles can be analyzed, for example, by X-ray fluorescence analysis (XRF) of the core particles obtained as precipitates.
[0080] <Cosmetic composition containing soap complex particles>
[0081] The cosmetic composition of the present embodiment includes the above-mentioned soap composite particles. Examples of cosmetic compositions containing soap composite particles include makeup cosmetic compositions such as foundation, liquid foundation, eyeshadow, blush, face powder, concealer, cheek, eyebrow powder, and highlighter; cleansing compositions such as cleansing compositions and facial wash compositions; skincare cosmetic compositions such as massage cream, moisture cream, and emulsion; body care cosmetic compositions such as bath additives, sunscreen, UV protection cream, and deodorant spray; basic cosmetic compositions such as makeup base; and hair care cosmetic compositions such as shampoo, conditioner, hair liquid, and hair color. These cosmetic compositions can be prepared by mixing and processing various raw materials in proportions suitable for their intended use.
[0082] The above cosmetic composition may contain the soap composite particles in a range of 0.5 mass% to 60 mass% relative to the total amount of the cosmetic composition. Preferably, the soap composite particles may be contained in a range of 1 mass% to 40 mass% relative to the total amount of the cosmetic composition, and more preferably, in a range of 2 mass% to 30 mass%. This is because if the content ratio of the soap composite particles is less than 0.5 mass%, it is difficult to feel the effect of improving skin texture when using the cosmetic composition, and if it exceeds 60 mass%, the effect corresponding to the amount of formulation cannot be expected, and it is also prone to causing problems in maintaining the quality or stability of the cosmetic composition.
[0083] In the above cosmetic composition, in addition to the soap composite particles, it is possible to incorporate various ingredients conventionally used in cosmetic compositions. Examples include ingredients such as pigments, surface treatment pigments, UV absorbers, physiologically active ingredients, emulsions, surfactants, fluorine compounds, resins, thickeners, preservatives, fragrances, moisturizers, salts, solvents, antioxidants, chelating agents, neutralizing agents, pH adjusters, and insect repellents. These ingredients may be incorporated in amounts that do not impair the effects of the cosmetic composition of the present invention.
[0084] The above cosmetic composition may include paraffinic solvents such as isododecane. Since the surface of the core particle of the above soap composite particle is hydrophobic, it is difficult for the inorganic oxide particles to detach, so the durability of the function of the metal soap particles is excellent. Furthermore, when the surface of the inorganic oxide is hydrophobic, the affinity of the inorganic oxide to the surface of the core particle is further increased, and the detachment of the inorganic oxide particles is further suppressed.
[0085] Although the present invention has been described above based on suitable embodiments, the present invention is not limited to the embodiments described above, and various modifications are possible within the scope of the essence of the invention.
[0086] Examples
[0087] The following describes embodiments of the present invention, but the present invention is not limited to these embodiments.
[0088] Preparation of Soap Composite Particles
[0089] Soap composite particles with inorganic oxides externally added to core particles containing saturated higher fatty acid salts and inorganic oxides were prepared by carrying out each of the following processes.
[0090] (Mixing process)
[0091] As shown in "saturated higher fatty acid salts" and "inorganic oxides added" in Tables 1 to 4, saturated higher fatty acid salts and inorganic oxides were each weighed and placed into a 20L Henschel mixer (FFM20 manufactured by Nippon Coke Industry Co., Ltd.) and stirred to obtain a mixed powder.
[0092] (Mixing process)
[0093] The mixed powder obtained from the mixing process was heated to 100 to 140°C in a twin-screw mixer (PCM-30, manufactured by Ikegai Co., Ltd.) to melt and mix. The molten mixture discharged from the mixer was passed through a cooled rolling roll to obtain a plate-shaped solid mixture.
[0094] (Grinding process)
[0095] A plate-shaped solid compound obtained from a mixing process was coarsely ground with a hammer mill to obtain a coarsely ground product of 0.5 to 3.0 mm. The coarsely ground product was finely ground with a jet mill (ULTRA SONIC JET MILL I-2, manufactured by Nippon Pneumatic Industry Co., Ltd.) to obtain a finely ground product with an average particle size of 3 to 20 μm based on volume.
[0096] (Classification process)
[0097] The finely ground material obtained from the grinding process had particles of 3 μm or less removed using an air-flow classifier (DS2UR product of Nippon Pneumatic Industry Co., Ltd.).
[0098] (Sphericalization process)
[0099] The classified powder obtained from the classification process was sphericalized by stirring for 20 minutes in a jacketed Henschel mixer 10L (Nippon Coke Product FM10) through which hot water heated to 60 to 90°C flowed.
[0100] (External Addition Process)
[0101] For the spherical core particles obtained by the spherical process, soap composite particles were obtained by externally adding inorganic oxides as shown in "Externally Added Inorganic Oxides" in Tables 1 to 4.
[0102] Core particle structure
[0103] Spherical core particles obtained from the spheroidization process were used as samples, and the structure of the core particles was measured by the following method. In addition, core particles separated from the external additives using the analysis method of the soap composite particles described above may also be used as samples.
[0104] (Circular drawing)
[0105] The sphericity of the core particles was based on values measured using a flow-type particle analysis device.
[0106] (Median diameter based on volume)
[0107] The median diameter (D50) was determined by measuring the volume distribution using the electrical change when the core particle passes through the aperture tube using a coulter counter.
[0108] Methods for Evaluating Skin Texture
[0109] A powder of soap compound particles, approximately one spoonful of earwax remover, was placed on the wrist of one arm, and the middle finger of the opposite hand was used to gently roll the powder across the skin in a circle with a diameter of 4 cm for 15 seconds to evaluate the tactile sensation using the middle finger and wrist. A panel of four evaluators (two adult males and two adult females) classified the user experience into categories and assigned scores to each category to conduct a sensorial evaluation. The evaluation categories and criteria are as follows.
[0110] (Skin texture evaluation items)
[0111] Spreadability… whether the powder spreads well on the skin when applied.
[0112] Adhesion… … whether the powder fills the pores well when applied.
[0113] Matteness… … whether the skin feel is good after application when applying the powder.
[0114] Lightness… … whether the weight sensation after application is small when applying powder.
[0115] Durability… whether the makeup has good durability when rubbed with a finger after applying the powder.
[0116] Softness… … whether the softness of the powder is good after application when applying the powder.
[0117] (Evaluation criteria for skin texture)
[0118] 5: Very excellent.
[0119] 4: Excellent.
[0120] 3: It is average.
[0121] 2: Falls.
[0122] 1: Drops significantly.
[0123] Manifestation of function
[0124] The expression of function of inorganic oxides was evaluated for each type of inorganic oxide according to the following evaluation criteria.
[0125] (Evaluation criteria for the manifestation of function)
[0126] 5: Exhibits the function of inorganic oxides.
[0127] 3: Slightly exhibits the function of inorganic oxides.
[0128] 1: Does not exhibit the function of inorganic oxides.
[0129] <Continuity of Function>
[0130] 9.5 g of a volatile organic solvent used in cosmetics was placed in a sample bottle, and 0.5 g of soap composite particle powder was added to it. The cap was closed, the bottle was placed on a vibrating table for stirring, and then left to stand for 24 hours in a room at a temperature of 20°C. The humidity was set within the range of ambient humidity (45–85%RH). The shape of the particles was observed using an optical microscope to determine if there was any change from the shape prior to immersion in the solvent. The sustainability of the function was evaluated according to the following evaluation criteria.
[0131] (Evaluation criteria for the sustainability of function)
[0132] 5: There was no change at all in the shape of the soap composite particles.
[0133] 3: There was some change in the shape of the soap composite particles.
[0134] 1: There was a change in the shape of the soap composite particles.
[0135] <Overall Evaluation>
[0136] The overall evaluation was conducted according to the following evaluation criteria based on the sum of scores obtained from three items: (1) skin texture, (2) manifestation of function, and (3) persistence of function.
[0137] (Evaluation criteria for the comprehensive evaluation)
[0138] +++: The total score was 15.
[0139] ++: The total score was 13 or 14.
[0140] +: The total score was 11 or 12.
[0141] -: The total score was less than 11.
[0142] <Evaluation Results>
[0143] The evaluation results are shown in Tables 1 to 4. In the column for "saturated higher fatty acid salts," fatty acid salts were indicated by a combination of the fatty acid name and the element symbol of the metal, such as "Ca stearate" representing "calcium stearate." In some comparative examples, unsaturated fatty acid salts were used.
[0144] Stearic acid (18 carbon atoms), lauric acid (12 carbon atoms), palmitic acid (16 carbon atoms), caprylic acid (8 carbon atoms), and behenic acid (22 carbon atoms) are straight-chain saturated fatty acids. In addition, oleic acid (18 carbon atoms, 1 double bond) and linoleic acid (18 carbon atoms, 2 double bonds) are straight-chain unsaturated fatty acids.
[0145] The weight parts of Tables 1 to 4 were set so that the total amount of added saturated higher fatty acid salts and inorganic oxides was 100 weight parts. For this reason, the value of the added amount (weight parts) of inorganic oxides is the same as the value of the content (weight%) of inorganic oxides in the core particles.
[0146] In the column for “hydrophobic treatment” in Tables 1 to 4, “None” was indicated when the inorganic oxide was not hydrophobic, “SiCp” for silane coupling treatment, and “SiOi” for silicon oil treatment.
[0147]
[0148]
[0149]
[0150]
[0151] In Examples 1 to 26, the overall evaluation was +++, ++, or +, making it possible to achieve both the improvement of skin texture and the sustainability of the function of the soap composite particles.
[0152] In Comparative Examples 1 to 4, the overall evaluation was negative.
[0153] Comparative Example 1 had a content of a specific metal oxide in the core particles exceeding 10 mass%, and the sustainability of the function was 1.
[0154] Comparative Example 2 had a circularity of less than 0.80, and the sustainability of the function became 1.
[0155] Comparative Examples 3 and 4 used unsaturated fatty acid salts instead of saturated higher fatty acid salts, but the skin tactile evaluation was low. Industrial applicability
[0156] The soap composite particles of the present invention can achieve both improved skin texture and sustained function of inorganic oxides, and can be used in the manufacture of cosmetics.
Claims
Claim 1 A soap composite particle comprising a core particle containing a saturated higher fatty acid salt and an inorganic oxide externally added to the core particle, wherein the sum of the contents of Li2O, Na2O, Al2O3, MgO, CaO, ZnO, BaO, TiO2, SiO2, Fe3O4, Fe2O3, and FeO in the core particle is 0 to 15 mass%, and the shape of the core particle is spherical with a sphericity of 0.80 to 1.
00. Claim 2 A soap composite particle according to claim 1, characterized in that the number of carbon atoms of the saturated higher fatty acid salt is within the range of 10 to 20. Claim 3 A soap composite particle according to claim 1, characterized in that the metal forming the saturated higher fatty acid salt is one or more of Li, Na, Al, Mg, Ca, Zn, and Ba. Claim 4 A soap composite particle according to claim 1, characterized in that the external amount of the inorganic oxide added per 100 parts by weight of the core particle is 0.01 to 15 parts by weight. Claim 5 A soap composite particle according to claim 1, characterized in that the inorganic oxide is one or more of zinc oxide, magnesium oxide, titanium dioxide, mica, talc, kaolin, sericite, silica, iron oxide, alumina, zirconia, and zeolite. Claim 6 A soap composite particle according to claim 1, characterized in that the inorganic oxide is hydrophobically treated. Claim 7 A soap composite particle according to claim 6, characterized in that the hydrophobization treatment is any one of silane coupling treatment, silicone oil treatment, long-chain alkyl silane treatment, fatty acid salt treatment, long-chain alkane treatment, long-chain alkene treatment, and long-chain alkyne treatment. Claim 8 A soap composite particle according to claim 1, characterized in that the average primary particle size of the inorganic oxide is 0.01 to 1.0 μm. Claim 9 A soap composite particle according to claim 1, characterized in that the volume-based median diameter of the core particle is greater than 3 μm and less than 20 μm. Claim 10 A method for manufacturing soap composite particles as described in claim 1, characterized by comprising: a grinding process for grinding a solid of a saturated higher fatty acid salt; a spheroidization process for spheroidizing the particles obtained by the grinding process; and an exfoliation process for exfoliating an inorganic oxide to the core particles obtained by the spheroidization process. Claim 11 A method for manufacturing soap composite particles as described in claim 1, characterized by comprising: a grinding process for grinding a solid of a saturated higher fatty acid salt; an exfoliation process for exfoliating an inorganic oxide to the particles obtained by the grinding process; and a spheroidization process for spheroidizing the particles obtained by the exfoliation process. Claim 12 A cosmetic composition characterized by incorporating soap composite particles as described in any one of claims 1 to 9.